A Proposed Framework for Integrating Interdisciplinary Approach in Undergraduate Architecture Design Education إطار مقترح لدمج النهج البيني في تعليم التصميم المعماري بمرحلة البكالوريوس - Hala Adeeb Fahmy (Journal of Urban Research)
The twenty-first century is witnessing continuous developments and diverse challenges that cannot be understood from a disciplinary perspective alone. This prompted academia to pay attention to the interdisciplinary approach as an entry to acquire the skills needed to face these challenges by creating solutions exceeding the scope of one discipline. Accordingly, and in the context of keenness to apply this approach to the local architectural academia, the study aims to provide a proposed vision for integrating the interdisciplinary approach into architectural design (AD) education through the creation of the Interdisciplinary Architectural Design Studio (IADS), to be included in undergraduate curricula. Therefore, the study first relied on the inductive approach to analyzing the latest literature that recorded experiences about this topic, and examples from the current situation have operationalized this approach in the international and local architectural academia to understand various aspects related to this integration. Secondly, the deductive analytical approach, by surveying to investigate the relevance and effectiveness of applying this approach in AD teaching and mechanisms on which the proposed studio should be based. The study concluded by transforming lessons learned into a proposed framework that can be applied and tested, and that aims to link artistic, scientific, theoretical, and practical aspects and provide a learning environment that encourages building the century competencies.